Some phytochemicals extracted from Cola acuminata leaf have antimalarial activity and improve derangements in haematological indices of Plasmodium berghei-infected mice - Lamiya, Abdulhafiz; Zailani, A. H; Adamu, M. G; Hammanadama, I. I; Dauda, E. M (International Journal of Pharmacological Research, 2020)
Malaria, a disease caused by Plasmodium species has been linked to high morbidity and mortality especially in sub-saharan Africa due to the resistance developed by the parasite against all the existing drugs, thus, necessitating the search for novel antimalarials. Colaacuminataleaf has been reported to possess antimalarial activity and also contain pharmacologically active phytochemicals including alkaloids, flavonoids, tannins and phenolics. The effects of these phytochemicalsin mice infected with Plasmodiumbergheiwas evaluated in this study. For each phytochemical, 7 groups (A-G) of eight mice each were used. Groups A and B served as normal and untreated controls respectively. Group C was treated with 20mg/Kg body weight of chloroquine and served as the treated control. Groups D, E and F were administered 12.5, 25 and 50 mg/kg body weight of the different phytochemicals while group F was treated with 50mg/Kg body weight of the phytochemicals only without parasite inoculation thus serving as extract control. Treatment commenced 72hrs after inoculation and was done once orally for four consecutive days after which parasitaemia was evaluated. All the phytochemicals were found to exhibit antimalarial activity in adose dependent manner. The mean survival time of all the experimental groups were also prolonged in a dose dependent manner compared to that of untreated control. Similarly, all the phytochemicals improved the altered haematological indicestowards normal.These phytochemicals of Colaacuminata exhibited significant antimalarial activitiesthus can be further studied in the search for novel antimalarial drugs.